2019
DOI: 10.20867/tosee.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Residents’ Support for Cultural Tourism Development

Abstract: Purpose -The main purpose of this paper is to find out the residents' perceptions and attitudes as well as what factors influence their support when cultural tourism development is concerned. City of Zagreb is chosen as research area as one of the most attractive continental destinations in Croatia that is hosting more and more visitors every year, so it was found necessary to find out the residents' perspective regarding this trend, particularly toward cultural tourism that has a great innovation potential. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…These results confirm those from previous studies [22,52,53]. Further, residents also agree that tourism does not negatively affect the customs and local traditions (2.28 ± 1.448), enhancing the idea that tourism has a positive impact on the cultural identity [54]. In contrast to other studies, the respondents do not consider that tourism has provided opportunities to restore and protect historic buildings.…”
Section: Discussionsupporting
confidence: 84%
“…These results confirm those from previous studies [22,52,53]. Further, residents also agree that tourism does not negatively affect the customs and local traditions (2.28 ± 1.448), enhancing the idea that tourism has a positive impact on the cultural identity [54]. In contrast to other studies, the respondents do not consider that tourism has provided opportunities to restore and protect historic buildings.…”
Section: Discussionsupporting
confidence: 84%
“…Given the importance of resident support for sustainable tourism development, many studies have examined the relationship between tourism impacts and attitudes toward tourism development (Uysal et al, 2016). Several authors have found that residents' perceived impacts of tourism significantly predict their support for tourism development, with stronger perceptions of positive impacts leading to greater support (Andereck and Vogt, 2000;Ap, 1992;Soldić Frleta and Đurkin Badurina, 2019;Vidal Rua, 2021). Vargas-Sánchez et al (2009) confirmed that the perception of tourism impacts (both positive and negative) is the most important factor determining residents' attitudes towards additional tourism development.…”
Section: 1) Residents Perceptions and Support For Tourismmentioning
confidence: 93%
“…Zero-waste initiative is a concept that emphasizes the reduction and reuse of waste as valuable resource [21]. Tourists recognize and support the concept of recycling, waste management and sustainable development with the concept of zero waste, but not all of them behave in accordance with the concept of zero waste and are still less concerned about saving water and energy consumption while traveling [22].…”
Section: Introductionmentioning
confidence: 99%